Analisis Good Corporate Governance Melalui Manajemen Risiko Berdasarkan QS. Yusuf Pada Bank Syariah Indonesia Tahun 2022 - Shaennon Agustina; Siti Nurhalizah Fitriani; Mohamad Djasuli (CV. ITTC INDONESIA, 2022)
Every corporation in the world of business, industry and banking must be able to implement good corporate governance because it is very important. Banks are an important component of the Indonesian economy and are very helpful in enhancing the strength of the country's banking sector. Therefore, increasing the implementation of Good Corporate Governance (GCG) is one of the efforts made. Several parties need to play a role in realizing good corporate governance, especially risk management. Because risk management here plays a role in analyzing potential risks and managing them. Descriptive qualitative methodology is used in this study. Based on the data used in this study, it was collected through primary research by utilizing the company's annual report.